Rapid and Dynamic Alternative Splicing Impacts the Arabidopsis Cold Response Transcriptome. Issue 7 (15th May 2018) - Calixto, Cristiane P.G.; Guo, Wenbin; James, Allan B.; Tzioutziou, Nikoleta A.; Entizne, Juan Carlos; Panter, Paige E.; Knight, Heather; Nimmo, Hugh G.; Zhang, Runxuan; Brown, John W.S.
Abstract : Alternative splicing is a major contributor to reprogramming of the transcriptome in response to cold. Abstract: Plants have adapted to tolerate and survive constantly changing environmental conditions by reprogramming gene expression The dynamics of the contribution of alternative splicing (AS) to stress responses are unknown. RNA-sequencing of a time-series of Arabidopsis thaliana plants exposed to cold determines the timing of significant AS changes. This shows a massive and rapid AS response with coincident waves of transcriptional and AS activity occurring in the first few hours of temperature reduction and further AS throughout the cold. In particular, hundreds of genes showed changes in expression due to rapidly occurring AS in response to cold ("early AS" genes); these included numerous novel cold-responsive transcription factors and splicing factors/RNA binding proteins regulated only by AS. The speed and sensitivity to small temperature changes of AS of some of these genes suggest that fine-tuning expression via AS pathways contributes to the thermo-plasticity of expression. Four early AS splicing regulatory genes have been shown previously to be required for freezing tolerance and acclimation; we provide evidence of a fifth gene, U2B"-LIKE . Such factors likely drive cascades of AS of downstream genes that, alongside transcription, modulate transcriptome reprogramming that together govern the physiological and survival responses of plants to low temperature.